Sand tiger shark Carcharias taurus mating season in the northwest Atlantic Ocean inferred from wound healing dynamics - Jennifer T. Wyffels; Joshua Riter; Carol S. Price; Kate Poelzl; Brenda Young; Tim Handsel; Laura E. Edsberg (Environmental Biology of Fishes, 2025)
All sharks and rays reproduce using internal fertilization. This necessitates males and females to be coupled tightly during copulation, and as a result, bite wounds associated with mating occur. The appearance of these bite wounds can be used to gauge the timeframe of mating activity without direct observation of copulation. A wound staging system was developed for the sand tiger shark Carcharias taurus through longitudinal observations of an aquarium-housed female that sustained a full-thickness mating wound, an injury that extends through the epidermis, dermis, and hypodermis, exposing underlying muscle. Four wound stages were established: (1) full-thickness, (2) healing, (3) closure, and (4) scar revision. The female’s stage 1 (full thickness) wound transitioned to stage 2 (healing) 2 weeks post-injury. Stage 3 (wound closure) was observed 3–6 weeks post-injury and stage 4 (scar revision) followed and persisted for the duration of the study, 35 weeks post-injury. The staging system was used to characterize the incidence, severity, and etiology of wounds for in situ sharks aggregating at North Carolina shipwreck sites from digital images contributed to the Spot A Shark USA database. There was a significant association between wound stage and its location or zone on the body as well as season of the year for males and females. Mating wounds on females corroborate a late spring and early summer mating season. The presence of stages 1 and 2 mating wounds on sand tiger sharks in North Carolina suggests the area is used for mating while females with stages 3 and 4 mating wounds provide evidence that the area also serves as gestation habitat for this species. This research highlights minimally invasive methodology that leverages citizen science divers to further characterize the reproductive life history of sand tiger sharks.